1994
DOI: 10.1111/j.1558-5646.1994.tb02195.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EVOLUTION OF CARBON ALLOCATION TO PLANT SECONDARY METABOLITES: A GENETIC ANALYSIS OF COST INDIPLACUS AURANTIACUS

Abstract: Diplacus aurantiacus contains large amounts of a leaf phenolic resin, an important deterrent to a leaf-eating caterpillar, Euphydryas chalcedona. The resin can also retard water loss during drought. Furthermore, the leaf resin content differs among plants and populations. This study investigates the existence of heritable variation (h ) in resin production and tests for a genetic correlation (r ) between carbon allocation to secondary metabolites and growth rate, as well as with three other vegetative traits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…For example, potential seed production is negatively correlated with furanocoumarin concentrations in Pastinaca sativa (Berenbaum et al 1986;Zangerl and Berenbaum 1997). Plant growth rate is negatively correlated with the production of leaf phenolic resin in Diplacus aurantiacus (Han and Lincoln 1994) and with plant chemicals that confer resistance to Fusarium oxysporium in Raphanus sativus L. cultivars (Hoffland et al 1996). The second type are ecological costs (Simms 1992), which are due to negative genetic correlations between the levels of defense against different organisms, the levels of defense against a single organism expressed in different environments, or different components of defense such as resistance and tolerance.…”
mentioning
confidence: 99%
“…For example, potential seed production is negatively correlated with furanocoumarin concentrations in Pastinaca sativa (Berenbaum et al 1986;Zangerl and Berenbaum 1997). Plant growth rate is negatively correlated with the production of leaf phenolic resin in Diplacus aurantiacus (Han and Lincoln 1994) and with plant chemicals that confer resistance to Fusarium oxysporium in Raphanus sativus L. cultivars (Hoffland et al 1996). The second type are ecological costs (Simms 1992), which are due to negative genetic correlations between the levels of defense against different organisms, the levels of defense against a single organism expressed in different environments, or different components of defense such as resistance and tolerance.…”
mentioning
confidence: 99%
“…Although herbivory selects for enhanced plant resistance, plants vary greatly in their resistance, both among species (2) and among genotypes within species (3). This indicates that being well defended may not always be the best strategy-most likely because allocation to resistance may physiologically constrain other investments (reviewed in refs.…”
mentioning
confidence: 99%
“…Berenbaum et al (1986) found negative genetic correlations between levels of defensive compounds and estimators of individual fecundity. Han and Lincoln (1994) found a significant negative genetic correlation between growth rate and levels of secondary metabolites in Diplacus aurantiacus. Many studies, including our own, have measured fitness components in controlled environments, where environmental variation may be reduced, or gene expression may be altered by novel environments.…”
Section: Resultsmentioning
confidence: 88%
“…Berenbaum et al (1986) showed a negative genetic correlation between insect resistance and fecundity in Pastinaca sativa. Han and Lincoln (1994) found a significant negative genetic correlation between growth rate and levels of secondary metabolites in Diplacus aurantiacus. In Escherichia coli, mutations causing resistance to virus T4 carry pleiotropic costs of resistance, which can be ameliorated by epistatic modifiers (Lenski 1988a,b).…”
mentioning
confidence: 88%